Dampak Citra Negara Asal Terhadap Niat Beli Pada Pasar Ponsel Pintar Melalui Citra Dan Sikap Merek - Editya, Aurellsya Jessica Putri; Rahayuningtyas , Tri Esti (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of country of origin on consumers’ purchase intention in the smartphone market by considering brand image and attitude toward the brand as mediating variables. Specifically, this research seeks to explain how perceptions of a product’s country of origin contribute to the formation of brand image and shape consumers’ attitudes toward the brand. In addition, this study examines the direct effect of country of origin on purchase intention, as well as the indirect effects through brand image and attitude toward the brand. A quantitative research approach was employed using an online questionnaire as the data collection technique. The respondents consisted of 244 active smartphone users in Indonesia aged between 17 and 40 years. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. The results indicate that all proposed hypotheses are supported. Country of origin has a positive and significant effect on brand image, attitude toward the brand, and purchase intention. Furthermore, brand image and attitude toward the brand significantly influence purchase intention. The findings also confirm the presence of mediating effects, including both partial mediation and sequential mediation, in which country of origin affects brand image, subsequently shapes attitude toward the brand, and ultimately enhances consumers’ purchase intention. Theoretically, this study contributes to the consumer behavior literature by reinforcing the role of country of origin as a strategic extrinsic cue that operates through a hierarchical evaluation process involving cognitive and affective components. Practically, the findings suggest that smartphone companies should integrate country-of-origin cues with brand positioning strategies and communication efforts aimed at strengthening brand image and fostering positive consumer attitudes to improve purchase intention in a highly competitive market.